POETRY AND CREATIVE THINKING IN TURKISH EDUCATION - Ahmet DEMİR (Fırat University, 2020)
Turkish education is text-focused and literary texts, and thus poetry, is one of the main educational tools of text-focused learning processes in Turkish education. Literary texts are a phenomenon that include direct creativity, creative thinking, and high imagination and is appropriate for the nature of the child. In Turkish education at secondary school level, many literary texts of different genres (fairy tales, poems, novels, stories, theaters, etc.) are used as tools for the development of comprehension skills depending on the development characteristics of the target audience. In addition, children are encouraged to create various types of literary texts to improve their narrative skills. The literary texts used in Turkish education are full of creative emotions, thoughts and imaginations for children and are a multifaceted inspiration for creative imagination and creative thinking for children. Poetry is also directly related to creative thinking, especially in terms of language features. In this study, it is pointed out that poetry is a gateway to creative thinking in Turkish education. The study was limited to secondary school level in order to concretize the subject in a certain area of Turkish education. In this respect, the subject is handled by giving examples from the textbooks of the secondary school Turkish course published by the Ministry of National Education in the 2018-2019 academic year. It is also a necessity to see poetry as a gateway to creative thinking, to shape learning processes in the direction of creative thinking and to act with awareness in this direction. It should not be overlooked that poetry plays an important role in developing creative thinking skills of students, especially in the context of creative language use. In this context, in this study, the relationship between poetry and ‘creativity’/‘creative thinking is examined. The relationships between ‘creative thinking’ and languages features of poetry texts such as rhetorical arts, metaphors, imagination, uncommon reconciliations, associativity are revealed.